Perspectives of operational additive manufacturing: Case Studies from the Czech aerospace industry - Jirsák, Petr; Brunet-Thornton, Richard (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
This manuscript examines the results of a quantitative and qualitative survey on Additive Manufacturing in the Czech Republic, specifically the adoption within the aerospace industry. The study conducted in 2016 and 2017 provides a general understanding of the implementation. To better gauge the experience, two intensive interviews provide a candid perspective of the challenges encountered. The discussion depicts the central issues that each enterprise encounters during this transition from traditional to Additive Manufacturing. The findings reveal that, although the transformation is on-going, a solid knowledge base remains a critical element to successful deployment.